Revascularization of an Autotransplanted Mature Tooth After Extraoral Root Resection: A Case Report - Juraj Marton; Michal Mozoľa; Radovan Žižka; Zdeněk Pokorný (Case Reports in Dentistry)
The outcome of tooth autotransplantation depends mainly on the transplant tooth’s anatomy—the type of donor tooth and the developmental stage of root formation. Mature teeth display a higher complication rate due to lower pulp revascularization potential, requiring root canal treatment (RCT) pre- or postoperatively to avoid postoperative complications, which extends treatment duration and cost. This report details a 39-year-old patient’s autotransplantation of a mature wisdom tooth to replace the first molar after unsuccessful root canal retreatment. During the surgery, an extraoral root resection of the transplanted tooth was performed prior to placement to avoid the need to elevate the Schneiderian membrane, which displayed imperfect healing following the surgical removal of a cystic lesion in the maxillary sinus. RCT was not performed before nor after the procedure. At the 3-year follow-up, the tooth was asymptomatic. The vitality of the autotransplanted tooth was difficult to determine using standard vitality tests, which depend on patients’ subjective responses, but the use of pulse oximetry objectively confirmed this. This case not only shows the possibility of a mature tooth transplant revascularization in an older patient but also gives a possible postoperative protocol of how to objectively confirm and measure the revascularization of the autotransplanted tooth.